Does Food Security Matter for Transition in Arab Countries? - Maystadt, Jean-François; Trinh Tan, Jean-François; Breisinger, Clemens (International Food Policy Research Institute, 2012)
Expectations are high that transition in Tunisia, Egypt, Libya, and Yemen will bring about more freedom, justice, and economic opportunities. However, experiences from other world regions show that countries in transition are at high risk of entering conflicts, which often come at large economic, social and political costs. In order to identify options on how conflict may be prevented in Arab transition countries, this paper assesses the key global drivers of conflicts based on a dataset from 1960 to 2010 and improved cross-country regression techniques. Results show that unlike in other studies where per capita incomes, inequality, and poor governance, among other factors, emerge as the major determinants of conflict, food security at macro- and micro-levels emerges as the main cause of conflicts in the Arab world. This “Arab exceptionalism in conflict” suggests that improving food security is not only important for improving the lives of rural and urban people; it is also likely to be the key for a peaceful transition.